The INFINITY study protocol: a retrospective cohort study on decision making and clinical impact of biomarker-driven precision oncology in routine clinical practice - Martens, Uwe Marc; Schröder, Jan; Bengsch, Fee; Sellmann, Ludger; Busies, Sabine; Frank-Gleich, Stefanie; Zaiss, Matthias; Decker, Thomas; Schneeweiss, Andreas; Schuler, Martin; Grebhardt, Sina; Zacharias, Stefan; et al. (BMC cancer, 2023)
Background: Precision oncology, defined as treatment of patients with targeted therapies matched to specific molecular alterations, has entered routine clinical practice. Particularly in patients with advanced cancer or hematologic malignancies, for whom no further standard therapies are available, this approach is increasingly applied as last resort option outside of the approved indication. However, data on patient outcomes are not systematically collected, analyzed, reported, and shared. We have initiated the INFINITY registry to provide evidence from routine clinical practice to fill this knowledge gap. Methods: INFINITY is a retrospective, non-interventional cohort study conducted at approximately 100 sites in Germany (office-based oncologists/hematologists and hospitals). We aim to include 500 patients with advanced solid tumors or hematologic malignancies who received a non-standard targeted therapy based on potentially actionable molecular alterations or biomarkers. INFINITY aims to provide insights into the use of precision oncology in routine clinical practice within Germany. We systematically collect details on patient and disease characteristics, molecular testing, clinical decision-making, treatment, and outcome. Discussion: INFINITY will provide evidence on the current biomarker landscape driving treatment decisions in routine clinical care. It will also provide insights on effectiveness of precision oncology approaches in general, and of specific drug class/alteration matches used outside their approved indications. Trial registration: The study is registered at ClinicalTrials.gov, NCT04389541.